Habitat-modulated shell shape and spatial segregation in a Patagonian false limpet (Siphonaria lessonii) - Livore, Juan Pablo (2018)
Environmental stressors that characterize intertidal habitats, such as exposure to air, thermal amplitude and wave action, influence biological patterns of distribution. The effects of these stressors on intertidal organisms are often associated with their shape and size. Rocky inter-tidal shores in Patagonia are particularly stressful environments in which a species of false limpet occurs abundantly in 2 contrasting habitats. Here we describe size and shape segregation of the false limpet Siphonaria lessonii across multiple shores on 2 contrasting shore levels where limpets are abundant, namely the high (HT) and mid (MT) intertidal. We tested for differences in resistance to desiccation, and recovery from heat stress, and were able to define 2 ecomorphs using classic and geometric morphometrics analysis. Individuals from the HT lost significantly less water under stressful heat conditions, and showed higher recovery rates than those from the MT. Limpets from the HT had a broad aperture, flatter margin and larger size. In contrast, individuals from the MT had a narrow aperture, arched margin and smaller size. Together these results suggest the existence of 2 ecomorphs modulated by each contrasting habitat. The observed small-scale spatial segregation of the 2 ecomorphs may provide ecological advantages by allowing the exploitation of resources from 2 different habitats. The 2 ecomorphs may provide S. lessonii with a broad thermal tolerance breadth, potentially improving resistance of the species to extreme climatic events.